The Effect of Training on Work Performance and Career Development: The Role of Motivation as Intervening Variable - Dewi Rama Niati; Zulkifli Musannip Efendi Siregar; Yudi Prayoga (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to determine the effect of training on work performance and career development by mediating work motivation. Respondents in this study were employees of PT. Asam Jawa in South Labuhanbatu Regency, amounting to 135 employees. Collecting data in this study using a questionnaire. The process of distributing questionnaires was carried out via online (Google form). The collected data is processed using path analysis using Amos Software Version 23. The results showed that training and motivation can improve job performance.  Training, motivation, and job performance can improve career development of employees at work. It is recommended to improve training program, motivation and work performance of employess. For further research, we suggest to increase the population and variables in order to get better results.